Literasi Digital Pada Anak Usia Dini: Urgensi Peran Orang Tua dalam Menyikapi Interaksi Anak dengan Teknologi Digital - Maulana Ahmad, Saidan; Sri Nurhayati; Prita Kartika (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The digital literacy of parents will serve as the primary example for preschool children in utilizing digital technology. The comprehension and selected mediation model chosen by parents will determine a child's development in using digital devices and media. This qualitative descriptive study aims to identify the role of parents in responding to the various productivity and phenomena that occur in their children during interactions with digital technology in their developmental stages. The study involves 29 parents of preschool children, 1 school principal, and 2 teachers at TK Plus Al Adalah. Data is collected through literature exploration, interviews, observations, and documentary studies. The collected data is analyzed through data reduction, presentation, and conclusion. The results of the study reveal that: 1) Parents can facilitate their children in accessing digital technology, but parental literacy and mediation are not yet fully effective and optimal. 2) Further efforts are needed to enhance parents' understanding of digital literacy and develop inclusive learning strategies for children through digital technology approaches. 3) It is inappropriate to perceive the development of digital technology and content on social media solely as consumable material, as it also represents a form of interaction that indirectly guides individuals in developing specific digitalization and understanding skills. 4) Therefore, parents and teachers require guidance from practitioners, especially regarding aspects of developing and integrating digital technology-based learning experiences for preschool children.